Unveiling the Nature of INTEGRAL Objects: a Review - Pietro Parisi (Acta Polytechnica CTU Proceedings)
Since its launch in October 2002, the INTEGRAL observatory has improved our knowledge of the hard X-ray sky above 20 keV, carrying out more than ten years of observations in the energy range from 5 keV to 8 MeV. The most recently published INTEGRAL/IBIS surveys listed more than seven hundred sources in the 20-100 keV band. Most of these objects are either Active Galaxies (AGNs) or X-ray binaries; a fraction of both classes is made of highly absorbed sources, often associated with dim optical counterparts. Despite the big eort in the identication process, a large part of these IBIS objects (~25% of them) still remains unclassied. Cross-correlation with archival catalogues and/or multiwaveband follow-up observations are of invaluable help to identify and properly classify this unknown objects, but only optical or IR spectroscopy with ground based telescopes in the Northern and Southern Hemisphere can reveal the real nature of these objects. In this work we report on source types that we nd among the unidentied objects in the most recent INTEGRAL surveys.